IbM Kelompok Usaha Produk Olahan Susu Segar Di Dusun Boyong Desa Hargobinangun, Sleman Yogyakarta - Ninik Sri Rahayu; Sri Indrawati (UII, 2014)
Micro, IBM's partner program (science and technology to the Community) are SMEs Heroine Boyong I (stick milk) and Heroine Boyong II (milk candy). Both are micro-scale industry based on fresh dairy product businesses.IBM program on SME partners focused on the aspects of production and management. All activities in the production aspect functioned to improve the capacity and quality of production and increase dairy product variants. While aspects of management consists of: marketing, financial administration and human resource capacity building functioned as a partner in running the business well.Outputs from the aspects of production activities are: lay out production in accordance with the concept of lean manufacturing, the addition of production capacity, increased efficiency of production of milk candy, increasing dairy product variants can be produced, the product is equipped with a production label and expiration date. In terms of management: managed to get a halal certificate from MUI, promotion of relevant equipment, attractive product design, wider marketing network, the use of social media for marketing, simple financial statements, bill of sale authorized, improved business mentality, and the ability of Partners in processing of fresh dairy products bertamba increased. Keywords: SMEs, science and technology transfer, production and management